Mortality Among Workers at Oak Ridge National Laboratory. Issue 7 (4th March 2013) - Richardson, David B.; Wing, Steve; Keil, Alexander; Wolf, Susanne
Abstract Background Workers employed at the Oak Ridge National Laboratory (ORNL) were potentially exposed to a range of chemical and physical hazards, many of which are poorly characterized. We compared the observed deaths among workers to expectations based upon US mortality rates. Methods The cohort included 22, 831 workers hired between January 1, 1943 and December 31, 1984. Vital status and cause of death information were ascertained through December 31, 2008. Standardized mortality ratios (SMRs) were computed separately for males and females using US and Tennessee mortality rates; SMRs for men were tabulated separately for monthly‐, weekly‐, and hourly‐paid workers. Results Hourly‐paid males had more deaths due to cancer of the pleura (SMR = 12.09, 95% CI: 4.44, 26.32), cancer of the bladder (SMR = 1.89, 95% CI: 1.26, 2.71), and leukemia (SMR = 1.33, 95% CI: 0.87, 1.93) than expected based on US mortality rates. Female workers also had more deaths than expected from cancer of the bladder (SMR = 2.20, 95% CI: 1.20, 3.69) and leukemia (SMR = 1.64, 95% CI: 1.09, 2.36). The pleural cancer excess has only appeared since the 1980s, approximately 40 years after the start of operations. The bladder cancer excess was larger among workers who also had worked at other Oak Ridge nuclear weapons facilities, while the leukemia excess was among people who had not worked at other DOE facilities. Conclusions Occupational hazards including asbestos and ionizing radiation may contribute to these excesses. Am. J. Ind. Med. 56:725–732, 2013. © 2013 Wiley Periodicals, Inc.